Medical and aesthetic improvement of photodamaged skin by the combination of intense pulsed light and photodynamic therapy with 10% aminolevulinic acid hydrochloride gel - Abrouk, Michael; Dong, Joanna; Waibel, Jill S. (Lasers in surgery and medicine, 2022)
Objective To evaluate the efficacy and safety of photodynamic therapy (PDT) with the novel 10% aminolevulinic acid (ALA) hydrochloride gel (10% ALA gel) and BF‐RhodoLED® light (635 nm; 37 J/cm2) in combination with intense pulsed light (IPL) to augment the medical and aesthetic improvement of photodamaged skin of the décolleté. Methods This was a single‐site prospective, randomized, intraindividual split chest pilot study with 20 female subjects with moderate to severe photodamage of the décolleté. Subjects were randomized to ALA‐PDT + IPL to one split‐side of the chest and ALA‐PDT only to the contralateral side. Three blinded raters assessed aesthetic improvement using the global aesthetic improvement scale (GAIS). Results Eighteen subjects completed the study. Superior GAIS results were achieved on the ALA‐PDT + IPL treatment side than on the ALA‐PDT only treatment side (p < 0.001) after 24 weeks of follow‐up. Conclusions ALA‐PDT using 10% ALA hydrochloride gel and BF‐RhodoLED® light had superior rejuvenation effects on the décolleté when combined with IPL compared to ALA‐PDT alone.